Perceptions Of Benefits And Risks Regarding Sukuk Investment Decisions Made By Students - Rachmawati, Desiana; Maulana, Adipura Danang; Ulfa, Rosiana (Dinasti Publisher, 2025)
The purpose of this study is to examine the influence of perceived benefits and perceived risks on students' decisions to invest in sukuk. The research was conducted on prospective investors who are students at STTKD Yogyakarta. Data were collected using a closed-ended questionnaire with a Likert scale distributed to 53 respondents and analyzed using multiple linear regression. The results show that perceived benefits have a positive and significant effect on students' sukuk investment decisions. This is evidenced by a t-value of 4.209 > 2.007 and a significance level of 0.000 < 0.05. The perception of sukuk as a more stable investment compared to other capital market products is a key consideration for student investors in making investment decisions. On the other hand, perceived risks do not influence students' decisions to invest in sukuk. This is evidenced by a t-value of 0.748 < 2.007 and a significance level of 0.733 > 0.05. Students do not heavily consider risks when deciding to invest in sukuk as a sharia-compliant capital market product.